Clinico epidemiological study of pitted keratolysis - Naik Chandra; Singh Gurcharan (Wolters Kluwer Medknow Publications, 2007)
Background: Pitted keratolysis is a common dermatological condition. However, very few studies are available on the clinical characteristics and epidemiological features of this disorder from India and abroad. Materials and Methods: Fifty patients from rural area of Kolar at Sri R.L.J.H. and S.N.R. Hospital, presenting with clinically distinctive lesions of pitted keratolysis were included in the study. Cases were interviewed with particular emphasis on triggering factors and findings were recorded. Investigations like Gram′s stain, culture studies, Wood′s ultraviolet light examination, histopathology etc, was done in selected cases to ascertain the clinical diagnosis. Results: Age of the patients varied from 20 to 40 years in 52% with male preponderance in 82% of cases. Duration of the disease varied from 15 days to five years, most of the patients were bare-footed farmers (62% of cases). Hyperhidrosis and pruritus were most frequently observed symptoms in 70% and 60% of patients. Most of the patients presented with the characteristic pits which varied from 1 to 50 in number in 56 % of cases, located predominantly on the pressure bearing areas in 92% of cases and depth of the pits varied from 1 to 2 mm in 60% of cases. Associated skin conditions recorded in present study were fissuring of soles in 38%, psoriasis 10%, dermatophyte infections in 6%, planter warts 6% and Corynebacterial triad and corn in 2% of patients each. Discussion: Affection of bare-footed individuals, male preponderance, presence of hyperhidrosis and occurrence of lesions over pressure bearing areas of soles, observed in the present study were consistent with earlier studies on the subject. However, pruritus as commonest presenting symptom reported by 60% patients in the present study, has not been documented in the previous studies. Conclusion: Pitted keratolysis is fairly common in bare footed male farmers of rural India. The condition is predominantly seen over the pressure bearing areas of sole and hyperhidrosis is common precipitating factor. Pruritus, a common presenting symptom observed in this study has not been reported earlier.